ANALISIS PENDAPATAN DAN KETAHANAN RUMAH TANGGA TANI (Studi Kasus: Desa Sei Buluh Kec. Teluk Mengkudu Kab. Serdang Bedagai) - Saragih, M.Sc, Faoeza Hafiz; saleh, khairul (Universitas Medan Area, 2017)
One of the aim national development is the improvement of food security where Sei Buluh village, Teluk Mengkudu district North Sumatra recommended as Agro Technopark area based on food crops. The aim of this study was to determine factors that affected the income and food security of farm households. The method used Two Stage Linear regression Square (2SLS). The results show that factors that affected farm income were the price of seed and land, meanwhile, factors that affected the share of food expenditure in the price of chicken, instant noodles prices, and farm income.